Fano resonances observed in helium nanodroplets - LaForge, Aaron; Regina, D.; Jabbari, Ghazal; Gokhberg, Kirill; Kryzhevoi, Nikolai V.; Krishnan, S. R.; Hess, M.; O'Keeffe, P.; Ciavardini, A.; Prince, K. C.; Richter, R.; Stienkemeier, F.; et al. (Physical review, 2016)
Doubly excited Rydberg states of helium (He) have been studied in nanodroplets using synchrotron radiation. Although qualitatively similar to their atomic counterparts, the Fano resonances in droplets are broader and exhibit blueshifts which increase for the higher excited states. However, varying the droplet size hardly affects the shapes of the resonances. Furthermore, additional dipole-forbidden resonances appear which are not seen in the He atom. We discuss these features in terms of localized atomic states perturbed by the surrounding He atoms.
Gesehen am 08.06.2020